BISNIS KELUARGA TANPA “PUTERA MAHKOTA” - Andreas Heryjanto (Universitas Bunda Mulia, 2018)
Business viability is a main goal of family business. However, leaders are usually reluctant to letoff their power, even tend to be in charge beyond the age of retirement. The most fatal consequence ofreluctancy to hand over the leadership to his successor is the occurrence of